Characterization of Graphite/ZnO Schottky Barriers Formed on Polar and Nonpolar ZnO Surfaces. Issue 2 (23rd November 2018) - Yatskiv, Roman; Tiagulskyi, Stanislav; Grym, Jan
Abstract : The authors demonstrate that the electrical properties of Schottky junctions fabricated by the deposition of colloidal graphite strongly depend on the crystallographic orientation of the ZnO substrate. The current‐voltage, capacitance‐voltage, and impedance measurements indicate that near‐ideal Schottky junctions form on c‐plane, while on a‐ and m‐plane the junctions are laterally inhomogeneous. This behavior is assigned to higher concentration of native point defects in the near‐surface region of nonpolar ZnO substrates. The authors further present an extended equivalent circuit model, which corresponds to actual structure of the junctions, and sheds light on their electrical transport properties. Abstract : Electrical properties of graphite/ZnO Schottky junctions strongly depend on the crystallographic orientation of the ZnO substrate. The current‐voltage, capacitance‐voltage, and impedance measurements indicate that near‐ideal Schottky junctions form on c‐plane, while on a‐ and m‐plane the junctions are laterally inhomogeneous. This behavior is assigned to higher concentration of native point defects in the near‐surface region of nonpolar ZnO substrates.